Meningkatkan Kompetensi Pedagogik Guru dalam Pembelajaran Berbasis Multi Sumber melalui Model Pembelajaran IODE di MI Nurul Huda 2 Surodinawan Prajuritkulon Kota Mojokerto - Muhammad Ihwan (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2019)
This research is motivated by (a) the number of teachers who consider books as the only source of learning so that they cannot apply multi-source based learning (b) there are still teachers who have not mastered the IODE learning model, (c) the number of teachers who are only competent in Special Learning Models but difficult to implement new learning models such as IODE, (d) not all teachers have the opportunity to attend KTSP training or training, and (e) the scarcity of MGMP Activities specifically addresses the IODE Learning Model, so that the IODE learning model still feels unfamiliar in MI Nurul Huda 2 Surodinawan Prariorkulon Mojokerto City. Intake, Organizing, Demonstration, and Disclosure (Express) students in receiving learning information is still lacking, this is indicated by the reluctance of students to learn Indonesian, work carelessly and less enthusiastic in learning, to overcome this, the writer needs to do a School of Action Research ( CAR). Realizing the symptoms or facts mentioned above, in this study the writer took the title